Teaching of programming and pedagogical strategies used in Brazil (Revista Contexto & Educação, 2023)
The new world scenario, political, economic and social, demands the need to develop pedagogical practices capable of enhancing the appropriation of knowledge in a more meaningful way and closer to reality. Among these innovative practices, the Teaching of Programming has gained more and more space as a promoter of a global cognitive ecology. This work carried out a content analysis in the articles of the main magazines in the area of Education, from 1996 to 2016, in order to elucidate how educational environments are transformed by Computer Programming, thus providing the student protagonism. The results show a combination of pedagogical strategies in the Brazilian context, which point to a "marriage" between the Teaching of Programming and Active Methodologies (81%). In this environment, the student is actively involved with his teaching-learning process, controlling and creating rhythms and new relationships with knowledge. It has also been verified that the "Programming Environments" broaden the understanding about the impacts of science and technology in society, seeking through learning by doing and collaborative learning, to guide real problem solving and assist in decision making, characteristics of lives immersed in Cyberculture.